Galangin ameliorates PTU-induced vitiligo in zebrafish and B16F10 cells by increasing melanogenesis through activation of the p38/JNK MAPK pathway - Wusiman, Zulipikaer; Zhang, Ai-Mei; Zhang, Shu-Shu; Zhao, Ping-Ping; Kang, Yu-Tong; Zhang, Yun; Li, Zhi-Jian; Huo, Shi-Xia (Frontiers in Pharmacology, 2025)
ObjectiveAlpinia officinarum Hance is a traditional herb in Xinjiang for the treatment of vitiligo, and galangin (GA) is a flavonoid isolated from its roots. However, its therapeutic mechanism remains unclear.MethodsIn this study, 1-phenyl-2-thiourea (PTU) was used to establish a vitiligo model in zebrafish. After successful modeling, different concentrations of GA (1 and 2 μM) were administered, and the distribution of melanin granules was observed by assaying the melanin content, masson-fontana staining and tyrosinase activity. Transcriptomic analysis and molecular docking were used to identify potential GA-related pathways and targets for improving vitiligo. In addition, we evaluated the proliferation of B16F10 cells by PTU induction and also observed cellular melanin distribution using masson-fontana staining. Finally, Western blot was performed to detect the proteins of the relevant pathways.ResultsThe results showed that GA significantly increased melanin production and tyrosinase activity in depigmented zebrafish. In addition, we found that GA decreased ROS and MDA levels and increased the expression of GSH, CAT and T-SOD. In addition, transcriptome analysis indicated that GA likely acts through the mitogen-activated protein kinase (MAPK) signaling pathway. GA has a strong binding affinity for important targets.GA significantly increased the expression of genes such as mapk8b, mapk14a, mapk3, mitf, tyr, tyrp1b, tyrp1a, dct, and oca2, and decreased the expression of genes such as expression of genes such as raf1 and egfr. In addition, GA enhanced the viability of B16F10 cells, increased intracellular melanin content, and increased the expression of proteins such as p38, JNK1/2/3, TYR, MITF, TRP1, TRP2, and so on.ConclusionGA increases melanin production and distribution, improves tyrosinase activity, upregulates the expression of related genes and proteins through activation of MAPK and tyrosine metabolic pathways, downregulates oxidative stress, and then regulates changes in melanin synthesis to improve vitiligo.